Will China relocate its labor-intensive factories to Africa, flying-geese style? - Terutomo Ozawa; Christian Bellak (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
The authors explore the China-side determinants of China's industrial relocation to sub-Saharan Africa, highlighting several hurdles to substantial translocation that would jump start local economic development.
Keywords: 330